Organizational factors influencing work-life balance and their impact on employees in the Banking industry in Vietnam - Dang, Minh Ngoc (2018)
The dissertation aims to explore the concept of work-to-family enrichment and its antecedents together with consequences in the case of bank employees in Vietnam. Another purpose of this thesis is to study the role of work-to-family enrichment in the connections between organizational interventions for work-life balance (job autonomy, work-life benefits and policies, and supervisor support) and two aspects of job outcomes (organizational commitment and job satisfaction). Our study applied the framework of Baral and Bhargava (2010) which was conducted in the context of India. A quantitative research method was applied in order to evaluate the scales and test the theoretical paradigm. Data were collected from 180 employees working in the Vietnamese banking sector through an online structured questionnaire. For the sake of hypothesis testing, a multiple regression was conducted using STATA software. Our findings reflect that autonomy in the workplace and supervisor support have the positive effect on work-to-family enrichment and both facets of job outcomes. In contrast, no significant relationships were shown between work-life benefits and policies (WLBPs) and any of the job outcomes. It can be found from the hierarchical regression analysis of this study that work-to-family enrichment performed a role of full mediation in associations between job autonomy and all job outcomes; and partial mediation in the link between supervisor and all job outcomes. There were significant limitations of the research involved in the generic scale of WLBPs, the modest sample size, the limited factors being tested and the generalization of the findings to name but a few. Regarding research implications, this study has the considerable contribution to the literature about positive work-family interface under a novel viewpoint from a developing country, as most of the previous research in this topic concentrated in developed nations. In terms of practical implications, the findings make a suggestion to employers and management about designing jobs to promote supervisor support and job autonomy, and to manage employee work-life balance as a whole to maximize individual and organizational outcomes.